Growing an Enhanced Culture of Polyphosphate Accumulating Organisms using a University of Cape Town Membrane Bioreactor (UCTMBR) System - Thela, Njabulo (Department of Civil Engineering, 2023)
Phosphorus (P) is a resource required by all living organisms and a key ingredient in fertilizers and P-based pesticides. The global increase in fertilizer demand due to the continuing increase in population and rising demand for high quality food present a risk to the current P reserves given that P is sourced from a non-renewable phosphate rock. To cope with the increased demand and promote the sustainable use of P, researchers have been investigating methods to recover P from numerous waste streams, including municipal wastewater. Between the two main P removal technology processes, namely chemical precipitation and enhanced biological phosphorus removal (EBPR), the EBPR process presents a greater potential for P recovery in a wastewater treatment plant (WWTP). This EBPR process utilizes polyphosphate accumulating organisms (PAOs), which can accumulate P as polyphosphate (a metal phosphate complex that requires much larger P quantities than the P used for nutritional purposes in the biomass anabolic process). The resulting P-rich sludge generated in EBPR activated sludge (AS) systems can be broken down during anaerobic digestion (AD; often used to treat sludge generated in WWTPs), which results in a release of the polyphosphate as orthophosphate and free metal counterions (mainly magnesium, potassium and calcium that formed part of the polyphosphate). The P released is hence found in the AD dewatering liquor that is generated during the AD sludge thickening process and can be used towards formation of struvite (via side stream struvite crystallization unit that processes AD dewatering liquor), which is a mineral product applied to supplement P in agriculture. The use of mathematical models in the design and optimization of WWTPs has significantly grown in popularity over the past few years, with the development of models that can predict the performance of different WWTP unit operations. However, the development of such models requires an in-depth understanding of the physiology of microorganisms responsible for mediation of the bioprocesses resulting in biological wastewater treatment. In the case of the EBPR process, the PAOs play a critical role. Hence a better understanding of the functions of these microorganisms can allow for greater accuracy in model predictions. The current research undertook to grow an enhanced culture of PAOs at a relatively high solids concentration. For this purpose, a laboratory-scale University of Cape Town Membrane Bioreactor Activated Sludge (UCTMBR AS) system was setup, operated, and tested. To place PAOs at an advantage, the system was fed influent rich in readily biodegradable chemical oxygen demand (RBCOD) in the form of propionate. An activated sludge biomass containing PAOs shows certain characteristics that are different from those displayed by biomass containing predominantly ordinary heterotrophic organisms (OHOs). Therefore, it was possible to ascertain the presence of PAOs in the UCTMBR AS system using wet chemistry analysis protocols. To check the accuracy and reliability of the results, chemical oxygen demand (COD), nitrogen (N), and phosphorus (P) mass balances were conducted around the system and found to be within the acceptable range. Through the careful analysis of the data collected, the fraction of PAOs (favPAO = XBG/Xv) in the bioreactor was found to be 0.62 mgAVSS/mgVSS, while that of OHOs (favOHO = XBH/Xv) was a mere 0.12 mgAVSS/mgVSS at 76 % steady state (where the percentage indicates the COD fraction of the synthetic feed comprising propionate). Evidence presented in the current manuscript shows that PAOs prefer propionate over acetate. It was also found that a high influent calcium concentration inhibits the growth of PAOs due to the formation of calcium phosphate precipitates. The presence of nitrate in the anaerobic zone significantly inhibited the PAO metabolism in the anaerobic reactor causing a deterioration in PAO activity. In summary, the current study shows that a laboratory-scale UCTMBR AS system can be used to grow an enhanced culture of PAOs at the relatively high concentrations of 3 849 mgVSS/l. Operating such a system can play an important role in the overall study of PAOs, ultimately leading to more accurate model predictions.